Guidance and recommendations for research assessment in SSH: Lessons learned in the GraspOS project - Delmazo, Carol; Mystakopoulos, Fotis (Zenodo (CERN European Organization for Nuclear Research), 2025)
Abstract This document presents guidance and recommendations for responsible research assessment in the Social Sciences and Humanities (SSH), drawing on lessons learned from the SSH pilot conducted within the GraspOS Horizon Europe project (2023-2025). Led by OPERAS Research Infrastructure, the pilot engaged diverse stakeholders through a Community of Practice and validation workshops to develop Open Science-aware assessment approaches responsive to SSH particularities. The document is structured in two parts. Part 1 offers four key guidelines for shaping effective assessment in SSH: involving the community in assessment design; considering values and context before selecting metrics; valuing Open Science practices and diverse outputs; and prioritising qualitative assessment, particularly peer review and narrative CVs. Part 2 provides specific recommendations aligned with the SCOPE Framework for research evaluation, tailoring each step, Start with values, Context considerations, Options for evaluating, Probe deeply, and Evaluate your evaluation, to the SSH domain. The guidance addresses the distinct challenges SSH faces in research assessment, including methodological diversity, the prevalence of books and multilingual publications, and the limitations of traditional bibliometric indicators. It emphasises value-led rather than data-driven assessment, the recognition of diverse scholarly outputs and activities, and the importance of embedding Open Science principles into evaluation systems. The document also identifies key risks such as gaming behaviours and structural biases, proposing mitigation strategies to ensure fair and inclusive assessment practices.